Tinjauan Hukum terhadap Hubungan Kerja: Tindakan Penahanan Ijazah Karyawan oleh Perusahaan Berdasarkan Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan - Aini, Nuzul Magfirotul; Ansari, Teuku Syarul (Peneliti.net, 2024)
The aim of this paper is to ascertain how business relations leading to the withholding of an employee's certificate by the company align with Law Number 13 of 2003 regarding Manpower. The paper explores the use of a certificate as a form of job security in the contractual agreement between the company and temporary workers. The study employs a standardizing legal technique and utilizes three analytical approaches: legal, applied, and historical. This research, categorized as standardizing juridical examination, focuses on legal synchronization. For this investigation, the authors conducted library research, gathering data from primary, secondary, and tertiary sources, including various libraries, print media, and online platforms.